CHEMICAL ABUNDANCES IN BINARIES WITH TWIN COMPONENTS - Lyubchik, Yu.; Martin, E.; Basri, G.; Pavlenko, Ya. (Одеські астрономічні публікації, 2017)
Procedure and some preliminary results of abundances determination in binaries with twin components from solar neighborhood are discussed. Numerical analysis were carried out by fits of synthetical spectra and COG to high resolution (R=50000) observed data. To fit the observations we used model atmospheres of Kurucz with different metallicities and (modified) VALD line list.